Kapłan ze znamieniem posługi - Prijatelj, Erika (Studia Pastoralne, 2026)
The relation of the priest to Jesus Christ, and in him to his Church, is found in the very being of the priest by virtue of his sacramental consecration and in his ministry. The priest, who reflects his Lord, Jesus Christ is the servant of Christ present in the Church as mystery, communion and mission. Thus, by his very nature and sacramental mission, the priest appears in the structure of the Church as a sign of the absolute priority and gratuitousness of the grace given to the Church by the risen Christ. Through the ministerial priesthood the Church becomes aware in faith that her being comes not from herself but from the grace of Christ in the Holy Spirit. Each priest, whether diocesan or religious, is united to the other members of this presbyterate on the basis of the sacrament of holy orders and by particular bonds of apostolic charity, ministry and fraternity All priests in fact, whether diocesan or religious, share in the one priesthood of Christ the head and shepherd. Finally, because their role and task within the Church do not replace but promote the baptismal priesthood of the entire People of God, leading it to its full ecclesial realization, priests have a positive and helping relationship to the whole community. They have to recognize and uphold the dignity of the ecclesial community serving the sacraments and helping faithfully the given people.